Тенденции изменения в маловодные и многоводные годы водного стока рек Беларуси в условиях потепления климата - Асадчая, М. А.; Кольмакова, Е. Г. (Минск : БГУ, 2014)
The problem of the climate changes impact on surface water resources in Belarus is considered. The results of the study of water flow changes in big and small rivers in the country in conditions of climate warming in the past quarter century are shown. The comparative analysis of the parameters of annual rivers` water flow in extreme water availability years is carried out for two periods – before climate warming and during this period. For the purpose of the research the years of minimum and maximum water availability for the entire period of instrumental observations is established by analytical methods. For the first time the study identified the regional differences in the change of water runoff distribution in the context of hydrological seasons in low and high water availability year on the example of the Western Dvina and Pripyat rivers` basins. = Рассмотрено влияние климатических изменений на поверхностные водные ресурсы Беларуси. Приведены результаты исследования изменения водного стока малых и больших рек страны в условиях потепления климата за последнюю четверть века. Выполнен сравнительный анализ параметров годового объема стока рек за два периода (до потепления и в период потепления) в экстремальные по водности годы. Для этого в целях исследования посредством аналитических методов установлены годы с минимальной и максимальной водностью за весь период инструментальных наблюдений. На примере речных бассейнов рек Западной Двины и Припяти впервые выявлены региональные различия в изменении внутригодового распределения водного стока рек в разрезе гидрологических сезонов в маловодные и многоводные годы.